Educational robotics in Primary Education. A case in Greece (Research, Society and Development, 2021)
In recent years, educational robotics is gaining ground in the educational policy of more and more places around the world in both formal and non-formal education programs. Also, the usefulness of educational robotics in special education for the treatment of deficits of students with Learning Disabilities, Attention Deficit Hyperactivity Disorder and Autism, especially at the level of student inclusion, is strongly supported. In the present work, the findings of a pilot educational research in a general education school are presented with the participation of students with special educational needs.